Cyber intelligence-driven risk : how to build and use cyber intelligence for business risk decisions - Moore, Richard O., III, 1971- (John Wiley & Sons, 2021)
"The objective of the book will be approached from building a functional cyber intelligence driven risk program and explaining in granular detail how each function and capability can be properly leveraged to make informed business decisions in the era of increased emergent cyber threats and attacks. Readers will be able to: Build, buy, or outsource a functioning cyber intelligence driven risk program Understand the functional capabilities needed to have an effective program Know how to turn cyber intelligence into business decisions Effectively use cyber intelligence to support Enterprise Risk Management programs Reduce the impact of cyber events through intelligence for many business operations leveraging new technologies. Discern how can an effective cyber intelligence driven risk program influence mergers and acquisitions and the benefits of predictive cyber intelligence analytics. Reduce loss from cyber events for the organization"--